2011
DOI: 10.4314/sajas.v40i4.65248
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lactobacilli to normalize production of corticosterone induced by unpleasant handling of broilers

Abstract: A study was conducted to investigate the effect of two Lactobacillus strains on hypothalamus pituitary adrenal (HPA) axis activity induced by supposedly unpleasant handling (UH) of broiler chickens. The three treatments were: (1) non-handled chicks fed basal diet (control); (2) unpleasantly handled-chicks fed basal diet (UH-BD) and (3) unpleasantly handled-chicks fed basal diet supplemented with the probiotic, lactobacilli (UH-BDL). Chicks were exposed to UH from days 1 to 21. Treatment UH-BDL received probiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In this study, the acetate production was the highest, followed by propionate and butyrate which showed the lowest cumulative production, in agreement with other researchers [98,99]. The butyrate concentration was lower compared to propionate, in contrast to other studies [95,100]. Isobutyric acid was significantly higher (P<0.01) in the LPM group than in the CON group.…”
Section: Concentration Of Short Chain Fatty Acids (Scfas) In Caecum C...supporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the acetate production was the highest, followed by propionate and butyrate which showed the lowest cumulative production, in agreement with other researchers [98,99]. The butyrate concentration was lower compared to propionate, in contrast to other studies [95,100]. Isobutyric acid was significantly higher (P<0.01) in the LPM group than in the CON group.…”
Section: Concentration Of Short Chain Fatty Acids (Scfas) In Caecum C...supporting
confidence: 92%
“…It is well known that crypt lengthening is mediated by a spectrum of local, immune, and neuro-humoral factors, as well as by diet composition [88,93,94]. It has been reported that CD is directly representative of the intestinal environment and may be used as an indicator of intestinal health [95].…”
Section: Histology Of the Small Intestinementioning
confidence: 99%
“…Physiologically, these changes may lead to depletion of muscle glycogen reserves and therefore affecting the rate and extent of pH decrease, which could affect meat quality (Debut et al 2003). On the other hand, stressful experience may disturb the balance of intestinal microbiota and lead to excessive growth of pathogens while decreasing the proportion of beneficial bacteria such as Lactobacilli and Bifidobacteria (Meimandipour et al 2010;Zhang et al 2016). Proliferation of Bifidobacteria and Lactobacilli in the gut can increase non-anxious behaviour in mouse through vagus nerve, maybe through bacteria-derived neuroactive elements (Saulnier et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the stress system, most studies to date identified effects of gut microbiota on basal CORT level in chickens. Manipulating microbiota via probiotic treatment did not alter basal CORT level in unpleasantly handled broilers 1 (Meimandipour et al, 2011), broilers (Cengiz et al, 2015;Yan et al, 2018) or laying hens, but it reduced basal ACTH level in laying hens (Lei et al, 2013). Similarly, prebiotic treatment did not alter basal CORT level in broilers (Houshmand et al, 2012).…”
Section: Chicken Studiesmentioning
confidence: 89%